Case Report: Multi organ dysfunction in a dog following massive paper wasp (Polistes rothneyi) envenomation - Lee, Jeong-Min; Lee, Seung-Keun; Lee, Sun-Tae (Frontiers in Veterinary Science, 2025)
Paper wasp (Polistes rothneyi) envenomation is an emerging public threat in Asian countries, but its clinical manifestations are limited in veterinary medicine. A 2-year-old male Yorkshire Terrier was evaluated for symptoms including vomiting, melena, and anuria, and upon presentation, exhibited lethargy and signs of jaundice. The dog had a history of being stung multiple times by paper wasps (Polistes rothneyi) 3 days prior to admission. On blood examination, anemia, severe azotemia, hyperbilirubinemia, and significant elevation of creatine kinase were noted. Treatment was initiated with epinephrine, glucocorticoids, antihistamines, and fluid therapy. Despite these interventions, the condition worsened, necessitating the initiation of continuous renal replacement therapy. However, the dog subsequently developed bradycardia and hypotension, leading to cardiac arrest 48 h after presentation. This is the first case report describing the clinical manifestation of dogs envenomated by paper wasps (Polistes rothneyi). Massive paper wasp envenomation can cause multiple organ lesions, including renal, hepatic, and gastrointestinal damage.